CERTIFIED HAJJ MANASIK GUIDANCE METHODS IN IMPROVING THE QUALITY OF CONGREGATION UNDERSTANDING AT THE MINISTRY OF HAJJ AND UMRAH OFFICE IN WEST JAKARTA - Ahmadih Rojalih Jawab; Hafizh Nur Falah; Muhamad Bilal Baihaqi; Siti Nurparoh (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2026)
ABSTRACT This study aims to evaluate the methods used by certified Hajj ritual (manasik) instructors in improving the quality of pilgrims’ understanding at the Ministry of Hajj and Umrah, West Jakarta Office. The background of this research is the limited understanding of some pilgrims regarding the procedures of Hajj rituals, despite having attended guidance sessions, as well as the constraints of facilities, time, and the insufficient number of instructors compared to the number of participants. The research employed a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The research subjects consisted of certified Hajj instructors, officials of the Ministry of Hajj and Umrah, and pilgrims departing in 2026. Data analysis was conducted inductively, focusing on the meanings and real-life experiences of the informants. The findings reveal that certified Hajj instructors applied various methods such as lectures, question-and-answer sessions, demonstrations, practice, and simulations. Among these, hands-on practice and simulations proved to be the most effective in strengthening pilgrims’ understanding. Several challenges were identified, including differences in pilgrims’ comprehension levels, limited facilities, time constraints, and lack of support from related parties. However, strategies such as dividing pilgrims into small groups, using teaching aids, and adjusting the language of instruction served as effective solutions. Overall, the presence of certified instructors had a significant impact on enhancing the understanding, readiness, and independence of pilgrims in West Jakarta Office. Keywords: Hajj rituals, certified instructors, quality of understanding, Ministry of Hajj and Umrah, West Jakarta Office.